Learn library of congress classification - Dittmann, Helena (DocMatrix, 2000)
This book covers the skill neccessary for a classifier using the Library Congress Classification ( LCC ) scheme, whether at a professional or paraprofessional level. It schemes: order the fields of knowledge in a systematic way; bring related items together in a helpful sequence; provide orderly access to the shelves either by browsing or via the catalog; provide an exact for an item on the sheves.